Manajemen pengolahan data pendaftaran praktik kerja lapangan (PKL) dan tugas akhir mahasiswa politeknik muara teweh - Maslianor; Noorhikmah Anisa Gayatri (Jurnal Pengetahuan dan Pendidikan, 2026)
Data Processing Management for Field Work Practice (PKL) Registration and Final Projects for Muara Teweh Polytechnic Students is carried out to accelerate academic services, especially in the registration and verification process, reduce the use of manual documents, reduce human error in data input and processing, facilitate report generation, and increase the transparency and accuracy of student academic data. Due to several constraints encountered in data processing, it is necessary to design a website-based system using the internet to facilitate the management of Field Work Practice (PKL) Registration and Final Projects. The author used observation, interviews, and literature study as data collection methods. The system design uses UML and ERD, and the programming languages ​​​​use PHP, XAMPP, MySQL, and CSS (Cascading Style Sheets) Database. The results of this study indicate that this system is able to make a significant contribution to improving the efficiency and accuracy of data management for Field Work Practice (PKL) Registration and Final Projects for Muara Teweh Polytechnic Students